Navigating Existential Literacy in the Age of Anxiety: A Failosophical Critique of Overthinking and the Crisis of Digital Citizenship - Andri Fransiskus Gultom (Konstruksi Sosial : Jurnal Penelitian Ilmu Sosial, 2025)
This study aims to examine the phenomenon of overthinking (OVT) among Generation Z in Indonesia through the lenses of "Existential Literacy" and "Failosophy." This study critiques how pathological anxiety and individual failure impact the subject's capacity as an authentic and resilient citizen amidst digital disruption. This study uses a qualitative approach with critical literacy analysis methods and philosophical reflection. The author integrates Elizabeth Day's thoughts on failure (via negativa) and Søren Kierkegaard's concept of "Fear and Trembling" to map the subject's psychological state against current social realities. The analysis shows that the rate of overthinking, which reaches 50% in Indonesian society, especially young women and the unemployed, is rooted in the failure to make an "existential leap" in the face of future absurdities. The data shows a correlation between excessive social media consumption (up to 15 hours per day) and the emergence of FOMO, FOPO, and rumination phenomena that paralyze decision-making. Existential literacy is proposed as a pedagogical strategy to transform failure from a mental burden into "fuel" for authentic existence. From a philosophy of citizenship perspective, existential resilience is a prerequisite for active citizenship. Individuals who are able to reconcile with failure and manage their OVT will have the courage to decide and take responsibility for their position in the public sphere, rather than being lost in the chaotic flow of information. This study offers novelty by conceptualizing overthinking not simply as a clinical-psychological problem, but rather as a failure of existential literacy that hinders individual agency in fulfilling the role of conscious and independent citizens.